State of the Art Compendium: Canadian Thoracic Society Recommendations for Management of Chronic Obstructive Pulmonary Disease. Issue 1 (2004) - O'Donnell, Denis E; Aaron, Shawn; Bourbeau, Jean; Hernandez, Paul; Marciniuk, Darcy; Balter, Meyer; Ford, Gordon; Gervais, Andre; Goldstein, Roger; Hodder, Rick; Maltais, Francois; Road, Jeremy
Abstract : Chronic obstructive pulmonary disease (COPD) is a common cause of disability and death in Canada. Moreover, morbidity and mortality from COPD continue to rise, and the economic burden is enormous. The main goal of the Canadian Thoracic Society's evidence-based guidelines is to optimize early diagnosis, prevention and management of COPD in Canada. The main message of the guidelines is that COPD is a preventable and treatable disease. Targeted spirometry is strongly recommended to expedite early diagnosis in smokers and former smokers who develop respiratory symptoms, and who are at risk for COPD. Smoking cessation remains the single most effective intervention to reduce the risk of COPD and to slow its progression. Education, especially self-management plans, are key interventions in COPD. Therapy should be escalated on an individual basis in accordance with the increasing severity of symptoms and disability. Long-acting anticholinergics and beta-2-agonist inhalers should be prescribed for patients who remain symptomatic despite short-acting bronchodilator therapy. Inhaled steroids should not be used as first line therapy in COPD, but have a role in preventing exacerbations in patients with more advanced disease who suffer recurrent exacerbations. Acute exacerbations of COPD cause significant morbidity and mortality and should be treated promptly with bronchodilators and a short course of oral steroids; antibiotics should be prescribed for purulent exacerbations. Patients with advanced COPD and respiratory failure require a comprehensive management plan that incorporates structured end-of-life care. Management strategies, consisting of combined modern pharmacotherapy and nonpharmacotherapeutic interventions (eg, pulmonary rehabilitation and exercise training) can effectively improve symptoms, activity levels and quality of life, even in patients with severe COPD.